PENGARUH METODE DISKUSI KELOMPOK DALAM EVALUASI HASIL BELAJAR MAHASISWA MENGGUNAKAN MINDMAP - Satrianawati, Satrianawati (Universitas Muhammadiyah Surakarta, 2015)
The aims of this research is to describe the influuence of group discussion method in the evaluation ofuniversity studentâ€™s learning output using mind-map strategy in the direction of â€œbangun ruang, kubus,balok, prisma, tabungâ€ to university student level V PGSD UAD Yogyakarta. This is experimentaldesign with the model of two group pretest-posttest design. The number of population are all of studentsfrom three class (VA, VB, VC), with random sampling from three class and the samples was 44 studentsfrom class VC. The techniques for collecting data were test with mind map product after studentâ€™sdiscussion in the group discussion. Data were collected from instrument of assessment output learningof mathematic analyzed with descriptive quantitative method. the result shows score of output learningover all in good category and exceed the minimum grades (KKM) were agreed. Because 80% ofuniversity students got minimum scorer in the good category. The result of t score obtained was 390,58 the t table was 2,000 with significance 5%, its means the hypothesis is accepted. Itâ€™s shows the influenceof group discussion method in the evaluation of university studentâ€™s learning output using mind-mapstrategy measurable cognition levels C1 and C2 university student in the direction of â€œbangun ruang,kubus, balok, prisma,and tabungâ€